Can adenosine triphosphate be a proxy measure in evaluation of hand disinfection effect?. Issue 3 (July 2020) - Breidablik, H.J.; Lysebo, D.E.; Johannesen, L.; Skare, Å.; Andersen, J.R.; Kleiven, O.T.
Summary: Contaminated hands may contribute to the transmission of pathogens. In the prevention of healthcare-associated infections the effect of disinfection methods should ideally be possible to measure in a simple way. Microbial cultivation is the reference standard, but it is a rather complicated and time-consuming procedure, and the use of swabs for measuring adenosine triphosphate (ATP) has become a much-used proxy measurement (bioluminescence). We evaluated the effect of three hand-disinfection methods on eradication of Escherichia coli from artificially contaminated hands, using cultivation and ATP measurements in parallel. ATP measurement was found to be an unsuitable method as this reflects the total amount of biomaterial present left on the hands, not only the viable bacteria.